Faktor-Faktor yang Berhubungan dengan Retensi Urine Pasca Operasi - Desak Nyoman Indra Dewi; Yuliati Amperaningsih; Giri Udani; Idawati Manurung; Ririn Sri Handayani (Jurnal Ilmu Kesehatan Indonesia, 2023)
Urinary retention is one of urinary system problem. Surgery estimated be able to overcome 11% the burden of disease in the world, but surgical procedures also cause postoperative complications due to certain risk factors. The epidemiology of postoperative urinary retention varies from 5-70%. According to data fromSurgical Polyclinic the number of surgeries about 3,307, an average of 276 per month, requires an assessment of risk factors related to urinary retention, to prevent further complications.Quantitative research, analytical design, cross sectional survey design. The population of all postoperative patients who made repeat visits at the Surgical Polyclinic, June 29th â€“ July 16th 2022. The sample using the Slovin formula is 69 with a non-random sampling technique, a purposive sampling approach. Data collection by interview and observation of patient medical records. The purpose of knowing the factors associated with postoperative urinary retention at the Surgical Polyclinic of RSUD Dr. H. Abdul Moeloek Lampung Province.Based on the results of the Chi Square test, there are three factors associated with postoperative urinary retention, namely age (p=0.017 OR 3.329 95% CI: 1.220-9.084), the type of surgery (p = 0.004 OR 5.5056 CI: 1.615-15.821), fluid balance factor (p=0.023 OR 0.156 95% CI: 0.035-0.690). Researchers suggest screening for early detection of disease and providing information media (leaflets, posters and audiovisuals) of healthy lifestyles, prevention and perioperative monitoring.Â Keywords: Urine Retention, Postoperative, Risk Factors